Identification of a novel filovirus in a common lancehead (Bothrops atrox (Linnaeus, 1758)) - HORIE, Masayuki (Journal of Veterinary Medical Science, 2021)
I performed metaviromic analysis of publicly available RNA-seq data from reptiles to understand the diversity of filoviruses (family Filoviridae). I identified a coding-complete sequence of a filovirus from the common lancehead (Bothrops atrox (Linnaeus, 1758)), tentatively named Tapajós virus (TAPV). Although the genome organization of TAPV is similar to mammalian filoviruses, our phylogenetic analysis showed that TAPV forms a cluster with a fish filovirus. However, TAPV is still distantly related to all the known filoviruses, suggesting that TAPV can be assigned as a species of a novel genus in Filoviridae. To our knowledge, this is the first report identifying a filovirus in reptiles, and thus contributes to a deeper understanding of the diversity and evolution of filoviruses.